Development of an Intelligent Prosthetic Ankle Joint: 2nd Report, Development of the 1st Prototype with Intelligent Prosthetic Ankle Joint - FURUSHO, Junji; AKAZAWA, Yasushi; KOYANAGI, Ken'ichi; NAKAGAKI, Satoko; LI, Chengqiu; NAKAGAWA, Akio; MORIMOTO, Shoji; OCHIAI, Kimihiro; HASHIMOTO, Yasunori (Transactions of the Japan Society of Mechanical Engineers Series C, 2006)
In the first report of this subject, a linear MR (Magneto-rheological) brake specially designed for prosthetic ankle joint to keep dorsal flexion in swing phase of gait has been presented. The brake using MR fluid has simple structure and can control its brake force with low voltage. MR brake is expected to improve the function of lower extremity orthosis for rehabilitation. In this report, we improved the developed MR brake, and made a prototype of intelligent prosthetic ankle joint. Walking experiments were carried out and the control performance of the developed intelligent prosthetic ankle joint was confirmed.